Jorge de Sena and Fernando Pessoa: for a modernist criticism - Oliveira, Lucas Laurentino (2024)
The present paper aims do analyze Jorge de Sena’s essay “O poeta é um fingidor” and through it investigate the autor’s critical composition, as well as its relations with Fernando Pessoa’s work and the modernisms of Orpheu and Presença. By the end, it aims to demonstrate that Jorge de Sena, through his reading of Pessoa, claims a form of literary criticism capable of comprehending the revolutionary language undertaken by the modernism.